(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The use of new technologies in businesses has made digital marketing more popular. It has completely changed the old ways of marketing and forced marketers to stay in touch with their purchaser or customers through the internet in order to sell their goods and services. So, when planning the best advertising and setting business goals, marketers must think about and analyse both the pros and cons of digital marketing. Why Digital marketing is used by all businesses because it is efficient and effective, and its popularity is growing faster every day. Businesses will soon find it easier to compete with big businesses on the same platform. So, digital marketing is now a must-have for both small and large businesses in the digital world we live in. This paper is a theoretical framework of evaluating digital marketing challenges & problems & associated solutions as well. For findings of the study , secondary data has been utilised.